Double auction with interdependent values: Incentives and efficiency - Fuhito Kojima; Takuro Yamashita (Theoretical Economics, 2017)
We study a double auction environment where buyers and sellers have interdependent valuations and multi-unit demand and supply. We propose a new mechanism that satisfies ex post incentive compatibility, individual rationality, feasibility, nonwastefulness, and no budget deficit. Moreover, this mechanism is asymptotically efficient in that the trade outcome in the mechanism converges to the efficient level as in a competitive equilibrium as the numbers of the buyers and sellers become large. Our mechanism is the first double auction mechanism with these properties in the interdependent values setting.
Keywords: D44; D47; D82; 330; Double auction; interdependent values; multi-unit demand and supply; ex post incentive compatibility; asymptotic efficiency